Two Amino Acid Changes at the N-Terminus of Transmissible Gastroenteritis Coronavirus Spike Protein Result in the Loss of Enteric Tropism - Ballesteros, M.L. (Virology, 1997)
To study the molecular basis of TGEV tropism, a collection of recombinants between the PUR46-MAD strain of transmissible gastroenteritis coronavirus (TGEV) infecting the enteric and respiratory tracts and the PTV strain, which only infects the respiratory tract, was generated. The recombinant isolation frequency was about 10(−9)recombinants per nucleotide and was 3.7-fold higher at the 5′-end of the S gene than in other areas of the genome. Thirty recombinants were plaque purified and characterized phenotypically and genetically. All recombinant viruses had a single crossover and had inherited the 5′- and 3′-halves of their genome from the enteric and respiratory parents, respectively. Recombinant viruses were classified into three groups, named 1 to 3, according to the location of the crossover. Group 1 recombinants had the crossover in the S gene, while in Groups 2 and 3 the crossovers were located in ORF1b and ORF1a, respectively. The tropism of the recombinants was studied. Recombinants of Group 1 had enteric and respiratory tropism, while Group 2 recombinants infected the respiratory, but not the enteric, tract. Viruses of both groups differed by two nucleotide changes at positions 214 and 655. Both changes may be in principle responsible for the loss of enteric tropism but only the change in nucleotide 655 was specifically found in the respiratory isolates and most likely this single nucleotide change, which leads to a substitution in amino acid 219 of the S protein, was responsible for the loss of enteric tropism in the closely related PUR-46 isolates. The available data indicate that in order to infect enteric tract cells with TGEV, two different domains of the S protein, mapping between amino acids 522 and 744 and around amino acid 219, respectively, are involved. The first domain binds to porcine aminopeptidase N, the cellular receptor for TGEV. In the other domain maps a second factor of undefined nature but which may be the binding site for a coreceptor essential for the enteric tropism of TGEV.